PROFESI DOKTER KANDUNGAN LAKI-LAKI DALAM PERSPEKTIF HUKUM ISLAM - Mulawarman, Harun (LP2M IAIN Mataram, 2014)
In line with the more wide access of Islamic people (especially woman) upon health and medicine, the issue of male obstetrician for woman raises in academic discourse. As such happened has reflected the necessity of Islam people to understand the boundary between man and woman in the context of healing which bound to medical ethics in the perspective Islamic law resources such as Quran, Hadiths, and the Ulama. In order to answer such question, this research is conducted through using library research. The result of this research shows that the Ulema have same perspective to this case in which they recognize that male obstetrician is able to see parts of patientâs body due to medical action. However, the patients must be accompanied by her mahram to avoid defamation, and there are other considerations such as (1) the Doctor must be cautious to Allah, trusted, fair, and having knowledge in medics. (2) The doctor does not open the patientâs body except for medical treatment. (3) As long as the patient is accompanied by her mahram, either her husband or her other family member (mostly woman who has been believed to accompanied the patient). (4) The doctor must be a Muslim, but if there is no muslim obstetrician, non Muslim doctor is also able to conduct medical treatment for the patients. If these prerequisites have been fulfilled, the doctor is able to see or touch the aurat of the patients because Islam is a religion which does not let its followers to live difficulties otherwise Islam emphasizes the maslahat and easiness of its followers.